Non-Destructive Testing of Dalle de Verre Windows by Fernand Léger and Alexandre Cingria in Switzerland - Johannes Hugenschmidt; Sophie Wolf; Christophe Gosselin (Heritage, 2023)
Dalle de verre windows consist of thick slabs of coloured glass set in a matrix of reinforced concrete. The invention of this special art form is closely linked to the developments in modern architecture in the first half of the 20th century that are characterized by using new technologies such as steel-frame construction, reinforced concrete and the increasing use of glass. Many of these windows are showing damage, some of it severe. Until now, the causes of damage have hardly been investigated and there is still no practical and suitable approach to the analysis of the state of conservation of dalle de verre glazings. One of the main objectives of an interdisciplinary project (2019–2021) was therefore to evaluate the potential of non-destructive techniques for the characterisation of and identification of damage of dalle the verre windows in their structural, physical and climatic context. Various non-destructive methods (Ground-Penetrating Radar, Electric resistivity, Half-cell potential, Ultrasonics, Induction, Magnet and Thermography) have been tested on two prominent dalle de verre examples: the windows created by Fernand Léger for the church of Saint-Germain d’Auxerre in Courfaivre (Swiss Jura mountains) and the large tripartite by Alexandre Cingria once decorating the choir window church of the Franciscan monastery at Fribourg, Switzerland. The results of the analyses presented in this paper provide valuable information on the advantages and limitations as well as the costs of the methods used.